Phosphate Accumulation Using MgO-Fe3O4/Agarose/Oxalic Acid Gel as a Diffusive Gradient in Thin Films (DGT) Binding Layer - Dinira, Layta; Rafif, Sullahudin Ahmad; Ulayya, Salwa; Rumhayati, Barlah; Darjito, Darjito; Sabarudin, Akhmad (EduChemia: Jurnal Kimia dan Pendidikan, 2025)
Monitoring phosphate concentration in waters is critical because excessive phosphate can lead to the death of aquatic organisms. Phosphate can be monitored via a passive sampler called Diffusion Gradient in Thin Films (DGT). This study combines MgO and Fe3O4 impregnated in agarose crosslinked with oxalic acid to accumulate phosphate from the solution as a DGT binding gel. The parameters observed in this study were MgO/Fe3O4 mass ratio (1:3, 1:1, 3:1), accumulation time (20, 40, 60, 120, 240, and 1440 min), phosphate concentration (0.2, 0.4, 0.6, 0.8, and 1 mg/L) and pH (4, 5, 6, 7, and 8) on phosphate accumulation. XRD pattern confirmed that the adsorbents used were MgO and Fe3O4. SEM analysis showed that the gel had an average pore size of 31.78 μm, and the adsorbents were evenly distributed. Gel with MgO/Fe3O4 mass ratio 3:1 can adsorb phosphate up to 97.19 ± 0.36%. The phosphate accumulation reached optimum after a minimum adsorption time of 4 hours and when the phosphate concentration in the solution was 0.4 mg/L. The solution's pH had no significant effect on phosphate accumulation. This study shows that MgO-Fe3O4/agarose/oxalic acid gel is an excellent binding gel to accumulate phosphate from water.